2020
DOI: 10.5530/amdhs.2020.2.8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Mental Health Challenges in Bangladesh

Abstract: Bangladesh is expected to face a rapid upraise of SARS-CoV-2 outbreak and the nation is in a state of locked down. Evidences suggests a nation suffers a wide range of mental health issues related to anxiety, fear, isolation, depression, panic, emotional outburst and sleep disturbances during COVID 19 pandemic.The psychological impairments are significant to the diagnosed cases, suspected cases, quarantine cases, health workers and their families and relatives. But the health individual spending times with an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 8 publications
0
17
1
Order By: Relevance
“…COVID-19-related stress and other impairments may be the result. (See Hossain et al (2020) and Odriozola-González et al (2020) for some very early opinions and results. )…”
Section: Resultsmentioning
confidence: 99%
“…COVID-19-related stress and other impairments may be the result. (See Hossain et al (2020) and Odriozola-González et al (2020) for some very early opinions and results. )…”
Section: Resultsmentioning
confidence: 99%
“…This situation created a confounding impact on their mental health status. 54 In Bangladesh, we observed several reported suicide cases during the COVID-19 pandemic as a result of getting infected, economic loss, social security, job security and emotional breakdown among marginalised wage earners. 55 56 An Indian case study suggested that COVID-19 may significantly impact the mental health status and influence suicidal ideation and suicide attempts among the affected people; other comorbid diseases may aggravate the situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of our study show, overall, the APC style had higher overall scores among all participants. [10] AVC style was significantly higher in males compared to females, in our study, and has been shown to be directly linked to fear, [9] stress, [19] physical illness, insomnia, [20] misleading information or spreading of unreliable information, [21][22][23] that was not examined in this study. Differences, by gender, in coping styles may need further exploration to further evaluate all related variables.…”
Section: Discussionmentioning
confidence: 67%
“…Widespread challenges, including mental health for frontline healthcare workers and the general population in Bangladesh during the Lockdown periods, continue to create further complications on an already overburdened health care system. [10] Prior to the COVID-19 pandemic, Bangladesh had already reported a severe burden on its healthcare sector, including issues related to inefficiency, scarcity of human resources, and corruption. [11] The COVID-19 pandemic added an additional burden to an already .…”
Section: Introductionmentioning
confidence: 99%